SPECIFICS OF ACADEMIC TEXT CONSTRUCTION - Mukan, Nataliya; Kozubska, Svitlana (Mountain School of Ukrainian Carpaty, 2021)
The article highlights the analysis results of scientific research as well as theorists and practitioners’ work’s generalization of the educational field on the academic text construction. It is revealed that scientific researches of domestic and foreign scientists are devoted to highlight various aspects of the problem of academic writing: development of academic literacy, academic and communicative competence formation, scientific language specificity and development of culture of its use, development of academic writing skills, etc. The used research methods (analysis, synthesis, generalization) are presented. The peculiarities of the research topic choice and the stages of the main activities of the researched topic are substantiated. The definition of the text as the basic unit of communication, as well as the academic text, which is prepared in accordance with the requirements of scientific style, and its content are expressed by the means of special scientific terminology and language tools. A three-component model of the academic text (sandwich technology / hamburger model) is presented, which covers key metatext elements: introduction, discussion, and conclusion. The relationship between the three components of the hamburger model of the academic text is reflected: the introduction presents the logic of the development of the author’s ideas; in the discussion part their presentation is realized; in the conclusions the author presents the conclusions from these ideas to the reader. The introductory, discussion and concluding parts specifics of the academic text construction are described. Conclusions are presented: the main characteristics of the academic text are as following: it contains the author’s idea (author’s vision of the research problem); its content contains knowledge, which highlights key terms and concepts. The academic text distinguishes integrity, which includes interconnected components, which contribute to the presentation of the content in a logical sequence.